2015
DOI: 10.1007/s11571-015-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

A cerebral blood flow evaluation during cognitive tasks following a cervical spinal cord injury: a case study using transcranial Doppler recordings

Abstract: A spinal cord injury (SCI) is one of the most common neurological disorders. In this paper, we examined the consequences of upper SCI in a male participant on the cerebral blood flow velocity. In particular, transcranial Doppler was used to study these effects through middle cerebral arteries (MCA) during resting-state periods and during cognitive challenges (non-verbal word-generation tasks and geometric-rotation tasks). Signal characteristics were analyzed from raw signals and envelope signals (maximum veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…There has been growing evidence that non-linear research studies have been devoted to analysis of EEG signals recorded from participants with pathological conditions such as Alzheimer's, dementia, depression, disturbed cognition, epilepsy, schizophrenia and sleep disorders as well as the brain function related to emotional states (Bleton and Sejdic 2015;Liu et al 2015;Poppy and Speckens 2015;Stam 2005). These studies shows that non-linear analyses are more in tune with nature of EEG signals and systems, thus, they are widely used in biological and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing evidence that non-linear research studies have been devoted to analysis of EEG signals recorded from participants with pathological conditions such as Alzheimer's, dementia, depression, disturbed cognition, epilepsy, schizophrenia and sleep disorders as well as the brain function related to emotional states (Bleton and Sejdic 2015;Liu et al 2015;Poppy and Speckens 2015;Stam 2005). These studies shows that non-linear analyses are more in tune with nature of EEG signals and systems, thus, they are widely used in biological and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, a study using TCD suggested that the difference in CA, which regulates CBF, rather than changes in BP, would be involved in symptomatic improvement in patients with sympathetic nervous system abnormalities due to an SCI [6]. Since then, several studies have investigated CBF control in patients with a high-level SCI using TCD [18,19]. CA involves myogenic, metabolic, and neurogenic control mechanisms, as well as systemic factors [20,21], and while static CA is well preserved in patients with a high-level SCI, dynamic CA is severely altered [22,23].…”
mentioning
confidence: 99%